Sovremennyj vzglyad na problemu morfobiomekhanicheskikh sostoyanij myshts v zavisimosti ot ikh siloboj dinamiki - Dorokhov, R. N.; Guba, V. P. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The purpose of this research was to study the dynamics of power of muscles on all amplitude of movement of joints of biokinematic parts and pairs in view of variant of biological development and somatic features on the pieces of ontogenesis: puerile, prepubertal, pubertal, juvenile and mature. An analyzed material is the fragment of the 13-years researches of children of Smolensk (aged 7 - 20). Examinations were conducted with the use of the metric method of the somatic diagnosis and the estimations of the biological variant of a development. The digital material illustrates ingroup variability of the power of muscles depending on the change of an articulate corner, the condition of muscles and a parity of power of bend and unbend muscles. The reasons of non-uniform change of power of muscles at uniform change of an articulate corner in the spherical joint are not clear.